Genotyping of Mycobacterium tuberculosis isolates from low endemic setting in south of Brazil - Noguti, Erika Noda (2009)
Tuberculosis (TB) is an important public health problem worldwide and the leading cause of deaths by an infectious agent. The objective of this study was provide information about genetic diversity of Mycobacterium tuberculosis, isolated from patients with pulmonary TB attended at the Laboratório de Ensino e Pesquisa em Análises Clínicas (LEPAC), using Spoligotyping and MIRU-VNTR methodologies. The results were reported in the paper "Genotyping of Mycobacterium tuberculosis isolates from low endemic setting in south of Brazil". From the Spoligotyping and MIRU-VNTR patterns of M. tuberculosis isolates dendrograms were constructed to evaluate the relationship of the isolates. The results show that TB in our region predominantly develops from endogenous reactivation of a latent infection. It was also carried out a comparison of discriminatory power between the methodologies used (Spoligotyping and MIRU-VNTR), obtaining better discriminatory capacity of the isolates combining the two methodologies.